Gazing at monsters: aesthetics, politics, and the national distribution of the sensible - Emre Keser (Journal of Aesthetics & Culture)
The Humanity Monument, a gigantic monument in Kars, a northeastern border city of Turkey, was intended to be visible from the Armenian side of the border and supposed to send messages of peace, apology, and reconciliation, implicitly alluding to the Armenian genocide of 1915. It depicted two halves of a human, or two humans, looking at each other in the eye. However, the then prime minister Erdoğan called it a “monster” in a public speech, leading to the monument’s demolition. He then suggested that his comments were just aesthetic judgments free of political convictions, echoing the familiar paradigm of “aestheticizing politics”: covering over or obscuring a political motive (“the ideological”) through the aesthetic. Although a useful understanding, this reduces both aesthetics and politics to ideology and establishes a binary between the sober critic and the a(n)esthetized masses. Instead, drawing upon Rancière’s notion of the aesthetic as what disturbs “the distribution of the sensible,” that is, the partition of roles, territories, parts, and visibilities, this essay reads the story of the monument as a disturbance of the national distribution of the sensible, pointing to the ways it embodies and reveals the monstrosity of the modern state founded upon the event of genocide and further complicates the distinctions between critic and masses, self and other, and gaze and object that the aesthetic ordering of the nation-state relies on.